Refractive Index and Temperature Sensing Based on an Optoelectronic Oscillator Incorporating a Fabry–Perot Fiber Bragg Grating - Yuguang Yang; Muguang Wang; Ya Shen; Yu Tang; Jing Zhang; Yue Wu; Shiying Xiao; Jingxuan Liu; Buzheng Wei; Qi Ding; Shuisheng Jian (IEEE Photonics Journal)
An ultrafast high-sensitivity refractive index (RI) and temperature-sensing system based on an optoelectronic oscillator (OEO) is proposed and demonstrated in this paper. A Fabry–Perot fiber Bragg grating (FP-FBG), which combines a gap with two FBGs in a silica V-shaped slot and characterizes a narrow notch in the reflection spectrum, is incorporated in the OEO to implement a microwave photonic filter and perform oscillating frequency selection. A microwave signal is generated by the OEO, whose oscillating frequency is determined by the center frequency of the FP-FBG notch, which varies with the surrounding environments. The RI or the temperature change can be accordingly measured by monitoring the frequency shift of the microwave signal using an electrical spectrum analyzer or a digital signal processor. An experiment is performed to verify the proposal. An RI sensitivity of 413.8 MHz/0.001RIU and a temperature sensitivity of 2516 MHz/°C are successively demonstrated.